Plasma Signaling Factors in Patients With Langerhans Cell Histiocytosis (LCH) Correlate With Relative Frequencies of LCH Cells and T Cells Within Lesions - Mitchell, Jenée; Kvedaraite, Egle; von Bahr Greenwood, Tatiana; Lourda, Magda; Henter, Jan-Inge; Berzins, Stuart P.; Kannourakis, George (Frontiers in Pediatrics, 2022)
Langerhans cell histiocytosis (LCH) lesions contain an inflammatory infiltrate of immune cells including myeloid-derived LCH cells. Cell-signalling proteins within the lesion environment suggest that LCH cells and T cells contribute majorly to the inflammation. Foxp3+ regulatory T cells (Tregs) are enriched in lesions and blood from patients with LCH and are likely involved in LCH pathogenesis. In contrast, mucosal associated invariant T (MAIT) cells are reduced in blood from these patients and the consequence of this is unknown. Serum/plasma levels of cytokines have been associated with LCH disease extent and may play a role in the recruitment of cells to lesions. We investigated whether plasma signalling factors differed between patients with active and non-active LCH. Cell-signalling factors (48 analytes total) were measured in patient plasma and cell populations from matched lesions and/or peripheral blood were enumerated. This study aimed at understanding whether plasma factors corresponded with LCH cells and/or LCH-associated T cell subsets in patients with LCH. We identified several associations between plasma factors and lesional/circulating immune cell populations, thus highlighting new factors as potentially important in LCH pathogenesis. This study highlights plasma cell-signalling factors that are associated with LCH cells, MAIT cells or Tregs in patients, thus they are potentially important in LCH pathogenesis. Further study into these associations is needed to determine whether these factors may become suitable prognostic indicators or therapeutic targets to benefit patients.